An Overview of Long COVID Support Services in Australia and International Clinical Guidelines, With a Proposed Care Model in a Global Context - Shiqi Luo; Zhen Zheng; Stephen Richard Bird; Magdalena Plebanski; Bernardo Figueiredo; Rebecca Jessup; Wanda Stelmach; Jennifer A. Robinson; Sophia Xenos; Micheal Olasoji; Dawn Wong Lit Wan; Jacob Sheahan; et al. (Frontiers Media S.A., 2023)
Objective: To identify gaps among Australian Long COVID support services and guidelines alongside recommendations for future health programs.Methods: Electronic databases and seven government health websites were searched for Long COVID-specific programs or clinics available in Australia as well as international and Australian management guidelines.Results: Five Long COVID specific guidelines and sixteen Australian services were reviewed. The majority of Australian services provided multidisciplinary rehabilitation programs with service models generally consistent with international and national guidelines. Most services included physiotherapists and psychologists. While early investigation at week 4 after contraction of COVID-19 is recommended by the Australian, UK and US guidelines, this was not consistently implemented.Conclusion: Besides Long COVID clinics, future solutions should focus on early identification that can be delivered by General Practitioners and all credentialed allied health professions. Study findings highlight an urgent need for innovative care models that address individual patient needs at an affordable cost. We propose a model that focuses on patient-led self-care with further enhancement via multi-disciplinary care tools.